Analisis Faktor Kualitas Hidup Lansia Penderita Hipertensi Wilayah Kerja Puskesmas Kauman Kabupaten Tulungagung - Disyacitta Putri Nugroho (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Hypertension is a chronic disease whose prevalence increases with age and significantly affects the quality of life among the elderly. Tulungagung Regency is one of the regions in East Java with a high number of hypertension cases among the elderly, with a prevalence of 35.62%. This study aimed to determine the factors that influence the quality of life of elderly people with hypertension in the Kauman Health Center working area. This research was an analytical observational study using a cross-sectional approach. The population consisted of all elderly individuals with hypertension within the Kauman Health Center’s coverage area. The sample included 140 respondents selected using a simple random sampling technique. The instruments used were questionnaires on individual characteristics, the MMAS-8 for medication adherence, the HPLP-II for healthy lifestyle behaviors, and the WHOQOL-BREF for assessing quality of life. Data were collected through interviews and documentation, then analyzed using univariate and bivariate (chi-square test) methods. The results showed that 64.3% of elderly people with hypertension had a poor quality of life. Factors that had a significant relationship with the quality of life among hypertensive elderly were nutritional intake, physical activity, duration of illness, stress management, and the presence of comorbidities. These findings indicate the need for integrated interventions focusing on promoting healthy lifestyles, improving stress management, and monitoring comorbid conditions to enhance the quality of life in elderly individuals with hypertension. It is expected that this study can serve as a reference in the development of more effective primary health care programs for the elderly population